An Assessment of Level of Reflective Thinking among Phase I and Phase II Medical Students—A Cross-sectional Descriptive Study - B Veena Umesh; Abhishekh Basavarajegowda; YC Nalini (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Introduction: As part of a competency-based curriculum, reflective writing (RW) is advocated right from the first MBBS, where students are expected to write reflections on the foundation course, early clinical exposure (ECE), self-directed learning (SDL), and AETCOM module in their log books. RW aimed to develop reflective thinking/reflective capacity among medical graduates to assist students in internalizing their learning in both cognitive and affective domains. The main objective of the study was to assess and compare the level of reflective thinking among first and second CBME batches of medical students using a self-administered structured questionnaire. Methodology: A self-administered questionnaire was shared with the students through Google Forms. A questionnaire was administered after the students were exposed to writing their reflections in the log books for each of their experiences in the foundation course, early clinical exposure, etc. Results: There were a total of 210 participants in the study, of which 151 of them belonged to Phase I, and 59 belonged to Phase II of MBBS. A mean score was then calculated for first- and second-year students for each of the four scales (understanding, habitual action, reflection, and critical reflection). The mean scores for habitual action and critical reflection are higher than those for understanding and reflection among Phase II medical students when compared to Phase I. Conclusions: This study provided insights from the students on their knowledge, attitude, and practice of reflective thinking among medical Phase I and Phase II medical students.